'A respite thing': A qualitative study of a creative arts leisure programme for family caregivers of people with dementia. Issue 1 (23rd April 2015) - Pienaar, Lorinda; Reynolds, Frances
This study explored the meanings of participating in a 5-week creative arts leisure programme designed for family caregivers of people with dementia, using interpretative phenomenological analysis. Eight carers attended and four who met the eligibility criteria agreed to be interviewed. Participants experienced the arts group as providing a sense of freedom and respite, strengthening identity through promoting achievement, offering social support through a collective focus on art- and craft-making and increasing resilience for coping with caring. Some found the 5-week programme too short. Benefits were linked to the security of knowing that loved ones with dementia were close by, being well cared for. Further research is needed into the long-term benefits of creative arts groups for promoting carer well-being.